Analisis Pemotongan dan Pemungutan Pajak Penghasilan Atas Alokasi Belanja Desa: Studi Empiris Desa Kembaran Kebumen - Subur Rizki Wahyuni; Primandita Fitriandi, S.S.T, M.S.E, M.A (JURNAL PAJAK INDONESIA, 2022)
This study aims to analyze problems faced by the village treasurer in fulfilling their tax obligations. This research is quantitative research by analyzing taxation data and various literatures, theories, regulations, and previous studies. The results show that the implementation of the obligation to withhold and collect Income Taxes (PPh) on the allocation of goods expenditures as the realization of Permendesa Number 11 of 2019 has been carried out by the village treasurer. The income taxes are Income Tax Article 21, Income Tax Article 22, Income Tax Article 23, and Income Tax Article 4 paragraph (2). Even though treasurer has carried out its obligations, it turns out that there are still some errors in the calculations, such as an error in determining tax base for Income Tax Article 21 for non-sustainable employees and non-sustainable employees. In addition, calculation error also occurs in the calculation of Income Tax Article 21 on income from government budget. In the calculation of Income Tax Article 23 and Income Tax Article 4 paragraph (2), there are still some calculation errors. This indicates that although the treasurer has formally complied with tax compliance, it turns out that treasurer is still lacking in complying with material compliance.